ANALISIS KELAYAKAN ISI BUKU TEKS PEMBELAJARAN MATEMATIKA KELAS IV SD/MI PADA MATERI PENGUKURAN SUDUT TERBITAN MEDIATAMA - Tamaledu, Febriana; Warsinah, Warsinah; Pangadongan, Fara Virgianita (Tunas: Jurnal Penelitian Pendidikan Dasar, 2021)
The purpose of the analysis of the feasibility of the contents of the mathematics learning textbooks for fourth grade SD/MI students in the Mediatama issue of Angle Measurement material is to determine the accuracy and suitability in the preparation of student textbooks based on KI and KD. The method in this writing uses a qualitative approach. The data collection technique used in this research is a documentary study with a content analysis approach. This data collection was carried out to determine the condition of students' textbooks in learning mathematics for grade IV SD/MI and their suitability with K-13. This is done as an effort to improve the quality of student textbooks in grade IV SD/MI mathematics learning used by educators and fourth grade students of SD/MI. In this paper, the documentation guidelines used are based on the knowledge and skills dimensions set by BSNP. Furthermore, data collection uses a scoring technique. This technique is done by putting a checklist on the scoring sheet according to the assessment criteria. The next data analysis technique is to calculate the percentage of each aspect. The results of the analysis on mathematics learning textbooks for grade IV SD/MI on Angle Measurement material published by Mediatama are as follows: (1) The feasibility of the knowledge dimension is 96% or in the very feasible category. (2) Eligibility on the skill dimension is 91% or in the very feasible category.